Editorial Note on the Special Issue on Education and Information Technologies - García Martínez, Verónica; Hernández Pérez, Jacinta; Silva Payró, Martha Patricia (Emerging Trends in Education, 2021)
The editors responsible for this issue, Jacinta Hernández Pérez, Verónical García Martínez y Martha Patricia Silva Payró, introduce its contents.